In search of lost insolence: Ferdydurke and cynicism - Jerzy Franczak (Przestrzenie Teorii)
This article is an attempt to interpret Witold Gombrowicz’s first novel in the context of cynicism, which is first conceptualized within the Foucauldian tradition as a practice of “frank speech” (parrhesia), and then, according to Peter Sloterdijk’s critical philosophy, as a form of modern consciousness based on inverted idealism. The opposition between an ancient subversive cynicism and its modern schizoid form allows one to analyze the complexity of Ferdydurke. In the course of interpretation it turns out that there are some intersecting planes: the protagonist searches in vain for lost insolence, but it is the author who manages to find it at the end of the novel.